2016
DOI: 10.3892/ol.2016.4498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urokinase-type plasminogen activator system in gastric cancer with peritoneal metastasis

Abstract: Abstract. Peritoneal metastasis is a primary cause of mortality in patients with gastric cancer. Urokinase-type plasminogen activator (uPA) has been demonstrated to be associated with tumor cell metastasis through the degradation of the extracellular matrix. The present study aimed to investigate the mechanisms of the uPA system in gastric cancer with peritoneal metastasis. Expression of uPA, uPA receptor (uPAR) and plasminogen activator inhibitor-1 (PAI-1) in four gastric cell lines (AGS, SGC7901, MKN45 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(31 reference statements)
2
5
0
Order By: Relevance
“…GC cells co‐cultured with adipocytes exhibited increased invasion ability (Figure 4). Previous studies have shown that IL‐6 and PAI‐1 are key factors that enhance the invasiveness of GC cells 33,34 . Our results were consistent with these reports; the expression levels of IL‐6 and PAI‐1 were significantly increased in the adipocytes co‐cultured with GC cells (Figure 3D).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…GC cells co‐cultured with adipocytes exhibited increased invasion ability (Figure 4). Previous studies have shown that IL‐6 and PAI‐1 are key factors that enhance the invasiveness of GC cells 33,34 . Our results were consistent with these reports; the expression levels of IL‐6 and PAI‐1 were significantly increased in the adipocytes co‐cultured with GC cells (Figure 3D).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that IL-6 and PAI-1 are key factors that enhance the invasiveness of GC cells. 33,34 Our results were consistent with these reports; the expression levels of IL-6 and PAI-1 were significantly increased in the adipocytes co-cultured with GC cells (Figure 3D). There is a possible underlying mechanism that increases the expression levels of IL-6 and PAI-1.…”
Section: Malignancy Of Gc Cells Induced By Conversion Of Adipocytic P...supporting
confidence: 91%
“…uPAS expression (uPA, uPAR, PAI-1), however, did not alter between malignant and non-malignant peritoneum within the patients with peritoneal metastases [88]. Translational investigations confirm the role of altered uPAS expressing cell lines in the development of peritoneal metastasis [89] and increased ascites formation [90].…”
Section: Tumour Expression and Association With Clinicopathological Featuresmentioning
confidence: 78%
“… 19 Based on the analysis to 105 GC specimens, Zhang et al 20 found that uPA and uPAR mRNA expression rates in infiltrating-type cases, stage III-IV, vessel invasion, lymphatic metastasis, and distant metastasis were significantly higher than those in expanding-type cases, stage I-II, non–vessel invasion, non–lymphatic metastasis, and non–distant metastasis, respectively, thereby suggesting that uPA and uPAR expressions can serve as prognostic markers of GC. Semiquantitative RT-PCR and ELISA measurements conducted by Ding et al 21 showed higher expressions of uPA and uPAR in peritoneal metastatic lesions than in normal peritoneal tissues. High levels of uPA and uPAR may predict an adverse outcome in patients with GC.…”
Section: Discussionmentioning
confidence: 96%